HUBUNGAN PENGETAHUAN, JARAK POSYANDU, DAN SUMBER INFORMASI DENGAN MINATNYA REMAJA KE POSYANDU DI WILAYAH KERJA UPTD PUSKESMAS PENYANDINGAN - Fitria Grama Depa; Murdiningsih; Putu Lusita Nati Indriani (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Adolescent posyandu is one form of Community Resource Health Effort (UKBM) which is managed and organized from, by, for and with the entire community including adolescents in empowering the community and providing convenience in obtaining health services for adolescents to improve the degree of health and healthy life skills of adolescents. T This type of research is observational research that is analytical in nature with a cross sectional design or approach. The sample in this study was adolescents aged 12 years to 18 years with a sample of 75 respondents. The type of data uses primary data, The results of bivariate research on the relationship between Knowledge, Posyandu Distance, and Information Sources with Adolescents' Interest in Posyandu based on the chi square statistical test of p-value knowledge 0.021 < 0.05, posyandu distance p-value 0.021 <0.05 and p-value information sources 0.027< 0.05 can be concluded that there is a relationship between knowledge, posyandu distance, and information sources simultaneously with adolescent interest in going to posyandu in the UPTD work area of the Ogan Komering Ulu Regency Pairing Health Center in 2023. The advice to the leadership of UPTD Puskesmas Penyandingan is to increase information about the Youth Posyandu by involving community leaders, health workers to provide counseling and counseling, as well as distributing brochures, billboards, and advertisements in print and electronic media so that the public knows the importance of the Youth Posyandu